Hypertension Induces Pro-arrhythmic Cardiac Connexome Disorders: Protective Effects of Treatment - Matus Sykora; Katarina Andelova; Barbara Szeiffova Bacova; Tamara Egan Benova; Adriana Martiskova; Vladimir Knezl; Narcis Tribulova (Biomolecules, 2023)
Prolonged population aging and unhealthy lifestyles contribute to the progressive prevalence of arterial hypertension. This is accompanied by low-grade inflammation and over time results in heart dysfunction and failure. Hypertension-induced myocardial structural and ion channel remodeling facilitates the development of both atrial and ventricular fibrillation, and these increase the risk of stroke and sudden death. Herein, we elucidate hypertension-induced impairment of “connexome” cardiomyocyte junctions. This complex ensures cell-to-cell adhesion and coupling for electrical and molecular signal propagation. Connexome dysfunction can be a key factor in promoting the occurrence of both cardiac arrhythmias and heart failure. However, the available literature indicates that arterial hypertension treatment can hamper myocardial structural remodeling, hypertrophy and/or fibrosis, and preserve connexome function. This suggests the pleiotropic effects of antihypertensive agents, including anti-inflammatory. Therefore, further research is required to identify specific molecular targets and pathways that will protect connexomes, and it is also necessary to develop new approaches to maintain heart function in patients suffering from primary or pulmonary arterial hypertension.